(untitled) (Proceedings of the International Conference on Public Health, 2017)
Metabolic syndrome is a clustering symptoms with cardiometabolic factors including obesity, insulin resistance, dyslipidemia, and elevated blood pressure. Several previous studies have shown the risk factors for metabolic syndrome, such as obesity, smoking, lack of physical activity and unhealthy diet. This study aims to identify risk factors associated with metabolic syndrome at the Faculty of Public Health Airlangga University. This research uses descriptive method with cross sectional design. Population in this research is Employee Faculty of Public Health University of Airlangga. Diagnosis of Metabolic syndrom was followed by National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III). Data analysis was performed by discriptive to determine the risk factors and metabolic syndrome. The results showed 59,46% % (22/37) respondents included in the metabolic syndrome. Metabolic syndrome was more common in women as much as 72,7 %. The component contributing to the presence of MetS is Fasting Plasma Glucose 100 % (p value 0,157), Waist Circumferences 100% (p value 0,000), High Density Lipid 81,8% (p value 0,0025), Diastolic Blood Pressure 45,4 % (p value 0,072),Trigliceride 22,7% (p value 0,36) dan Sistolic Blood Pressure (p value 0,632). The Risk Factor of Metabolic Syndrom included increase Added Sugar (90,9%), Sodium (77,27%), less consume fruits (72,7%), less consume vegetables (86,4%), Less consume Gandum(86,4%) and less than 60 minutes of physical activity (77,3%) , Smoking (9,09%).